Relationship of leg and joint stiffness during basic and sports specific tasks in high level athletes - Millet, E.; Moresi, M.; Watsford, M.; Taylor, P.; Greene, D. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to assess the stiffness relationship between basic jumping tasks and sports specific tasks, and the underlying joint stiffness contributions which contribute to leg stiffness modulation. Forty-seven high level female athletes from varying training backgrounds completed a maximal countermovement jump, drop jump, horizontal jump, 50 m sprint, change of direction cutting task and repetitive hopping. Pearson`s correlations or their non-parametric equivalent identified no relationship between basic jumping and sports specific tasks, however the repetitive hopping task exhibited a moderate relationship to each disciplines relevant sports specific task. Furthermore, joint stiffness contributions appeared to be unique to each athletic group. Results of this study appear to suggest sports specific tasks are superior screening tools for athletes.